The frontal eye field is involved in visual vector inversion in humans - a theta burst stimulation study - Jaun-Frutiger, K; Cazzoli, D; Müri, R; Bassetti, C; Nyffeler, T (Public Library of Science, 2013)
In the antisaccade task, subjects are requested to suppress a reflexive saccade towards a visual target and to perform a saccade towards the opposite side. In addition, in order to reproduce an accurate saccadic amplitude, the visual saccade vector (i.e., the distance between a central fixation point and the peripheral target) must be exactly inverted from one visual hemifield to the other. Results from recent studies using a correlational approach (i.e., fMRI, MEG) suggest that not only the posterior parietal cortex (PPC) but also the frontal eye field (FEF) might play an important role in such a visual vector inversion process. In order to assess whether the FEF contributes to visual vector inversion, we applied an interference approach with continuous theta burst stimulation (cTBS) during a memory-guided antisaccade task. In 10 healthy subjects, one train of cTBS was applied over the right FEF prior to a memory-guided antisaccade task. In comparison to the performance without stimulation or with sham stimulation, cTBS over the right FEF induced a hypometric gain for rightward but not leftward antisaccades. These results obtained with an interference approach confirm that the FEF is also involved in the process of visual vector inversion.